Analysis of potential superficial manifestations of liquefaction through severity indices from CPT data applied to the area of Jacó, Costa Rica - Montalva, Gonzalo (2023)
Possible surface manifestations of liquefaction were evaluated by means of severity indices, at a regional scale for the Jacó area, using information generated by 15 CPTu, estimating the seismic demand in a deterministic manner for 24 scenarios, for expected accelerations from ground motion prediction equations for Central America, considering crustal and subduction earthquakes, both intraplate and interplate. The results allow the identification of three areas where different levels of damage would be expected, depending on the seismic hazard represented in the analyzes by means of the magnitude of an earthquake and the accelerations that it could produce, and prioritize those to be investigated in greater detail for the development of private projects, public infrastructure and the location of essential buildings. The usefulness of the results is based on guiding municipal and emergency authorities to anticipate the response to the occurrence of an analysis scenario or another with intermediate conditions, knowing in advance the distribution of the sites where the damage could be greater in order to guide the immediate response and recovery efforts. It is expected that the results of this project, although preliminary, will serve as an input for the management of the risk associated with liquefaction through engineering and other measures, for purposes of land use planning and for the development of public policies for the district of Jacó, as could be a regulatory plan.